Oxidised low density Lipoprotein decreases HIT-T15 pancreatic beta cells viability decrease in antioxidant activities - Zunika, A.; Muna, Sabri; Rina, S. (malaysian society of applied biology, 2017)
Increased serum levels of oxidised low density lipoprotein (oxLDL) as found in patients with Type 2 diabetes, can induce severe oxidative stress in exposed cells which then can lead to cell death. Our study aimed to determine how the decreased cells antioxidant status of pancreatic beta cells induced by oxLDL affects their viability. We used various concentrations of CuCl2 oxidised LDL to determine its cytotoxic effect as well as the influence on the antioxidant enzymes activity in HIT-T15 pancreatic beta cells. A significant cellular formation of reactive oxygen species (ROS) was detected within 3 hours incubation of HIT-T15 pancreatic beta cells with 1.5 mg/mL of oxLDL. The formation of ROS was accompanied by a simultaneously loss of cellular glutathione. However, a significant reduction in cell viability was only measured after 10 hours incubation with oxLDL. The enzymatic activities of catalase and peroxidase remained unchanged for 24 hours. These results suggest that loss of glutathione induced by oxLDL is not sufficient to cause HIT-T15 cell death as they can be still protected from cytotoxic effects of oxLDL by the other antioxidant defenses such as catalase and peroxidase.